GROWING WITH THE HOLY FATHERS: "ABBA" (THE ELDER), "THEŌRIA" AND "PHRONÊMA EKKLÊSIAS", A "HERMENEUTICAL SPIRAL" DERIVED FROM THE ASCETICAL "PRAXIS"OF THE WORD - TĂNASE, Nichifor (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2016)
It is argued that the return to the biblical faith should find a parallel in a Return to the Fathers. Early Christian thought was biblical, and one of the lasting accomplishments of the patristic period was to forge a way of thinking which was scriptural in language and inspiration. Forgetful of this truth, the Holy Fathers have been isolated from the Scripture and there is therefore an imperative to seek to relate more closely the two. A particular hermeneutical perspective called theoria - an inspired vision of the Divine Truth, shaped their works. For Holy Fathers, exegesis never had a purpose in itself; rather patristic hermeneutics directly addressed the reader's life situation. As an antidote to the chasm between modern and pre-modern exegesis we propose the advice of Christopher A. Hall: Read the Bible holistically with the Fathers, which if actualized, would mean that the Church would recognize that it possesses a living Truth, one that cannot be limited purely to the biblical text. Further, it is proposed that Christ Himself is to be the hermeneutic principle or the principle of interpretation. The Bible does not contain its own principle of interpretation Orthodoxy operates in a closed hermeneutic circle through the dynamic that exists between Scripture and Tradition (the permanent presence of God). Unlike some former approaches to biblical interpretation, many of today’s scholars do not see this circular process as an obstacle to biblical exegesis, but understand it in terms of a hermeneutical spiral (G. Osborne), which describes the interaction between text and interpreter. The hermeneutical spiral takes place via the interaction of inductive and deductive research and via the movement from biblical to systematic and to homiletical theology. Finally, it is argued that the hermeneutical bridge between the word of Scripture and the present life of the Church as thus understood could be strengthened by rediscovering the hermeneutic function of the Holy Spirit, His continuing work of inspiration that allows the Word of God to be interpreted again, in any time and for each new generation.